A new method for detecting micro‐fragments of biodegradable mulch films containing poly(butylene adipate‐co‐terephthalate) (PBAT) in soil. Issue 1 (28th December 2021) - Wortman, Sam E.; Jeske, Elizabeth; Samuelson, Mitchell B.; Drijber, Rhae
Abstract: Biodegradable mulch (BDM) is a potentially sustainable alternative to polyethylene plastic mulch film for intensive crop production. Certified BDMs must demonstrate >90% biodegradation in compost and agricultural soil, but the environmental fate of BDM micro‐fragments is usually not measured. While using fatty acid methyl ester (FAME) analysis to study changes in soil microbial communities under different BDMs and management conditions, two peaks were detected by gas chromatography that were derived from a BDM containing poly(butylene adipate‐ co ‐terephthalate) (PBAT). The largest peak was identified as 1, 4‐benzenedicarboxylic acid, dimethyl ester, or dimethyl terephthalate (DMT). The smaller peak was hexanedioic acid dimethyl ester or dimethyl adipate. From this observation we hypothesized that the FAME method could be used to detect and quantify micro‐fragments (<5 mm in length) of PBAT‐containing BDM in soil. To test this, fragments of two commercially available BDMs were added to soil and extracted for FAME analyses. Linear relationships were observed between DMT and mulch mass added to soil for both BDMs when the initial mass of fragments was <3.5 mg ( r 2   > .99). Based on our findings, the FAME method could be redeployed to study the environmental fate and possible accumulation of BDM micro‐fragments in soil over time. Core Ideas: Small fragments of biodegradable mulch are difficult to trace and extract from soil. Many biodegradable mulch films contain poly (butylene adipate‐ co ‐terephthalate) (PBAT). Methanolysis of PBAT produces dimethyl terephthalate (DMT) and dimethyl adipate. Fatty acid methyl ester–extracted DMT correlates with initial mulch mass added to soil. Tracing DMT in soil improves knowledge about environmental fate of biodegradable plastics.